In vitro fermentation characteristics of the dietary fiber in bamboo (Phyllostachys edulis) shoots and its regulatory effects on the intestinal microbiota and metabolites. (15th March 2023) - Wu, Weijie; Li, Qi; Chen, Hangjun; Fang, Xiangjun; Niu, Ben; Liu, Ruiling; Mu, Honglei; Gao, Haiyan
Highlights: The carbohydrate utilization rate of BSDF-1 was 26.59%, which increased SCFAs. Abundances of Alistipes and Lactobacillus increased after BDSF-1 fermentation. BSDF-1 reduced the cadaverine increasing induced by DSS. BSDF-1 regulated the metabolism of the intestinal microbiota and the host. Abstract: The effects of bamboo ( Phyllostachys edulis) shoot dietary fiber (BSDF-1) on ulcerative colitis (UC) are unclear. Therefore, we performed an in vitro glycolysis study of intestinal microbiota samples, based on 16S rDNA sequencing and determining the metabolites in non-targeted colonic fecal fermentation broth. After a 48 h fermentation, the pH of the fermentation broth decreased significantly ( p  < 0.05) with the dextran sulfate sodium group (referred to here as the Mod group). The carbohydrate utilization rate was 26.59 %, and the total short-chain fatty acid content was 16.46 ± 0.71 mmol/L. The abundances of Alistipes and Lactobacillus increased after BDSF-1 fermentation, whereas those of Escherichia-Shigella, Enterococcus, and Proteus significantly decreased. BSDF-1 altered the levels of 17 metabolites in the Mod group after fermentation for 48 h, which reduced the cadaverine increasing induced by DSS. These results indicate that BSDF-1 can regulate the metabolism of the intestinal microbiota and the host, suggesting its use as a promising therapeutic strategy.